Legal Discovery Through Judicial Activism By Judges In Criminal Cases - Situmorang, Septriono; Nurini Aprilianda; Lucky Endrawati (Mahadi: Indonesia Journal of Law, 2025)
In exercising the authority to decide criminal cases, Judges sometimes cannot decide proportionally according to their beliefs because they are often faced with binding to written laws that are rigid, both material and formal criminal law. So that in order to resolve disputes it is felt that Judges must play an active role in using a new rule or changing an old rule, that is where Judges create law (Judge made law) through Judicial Activism. The purpose of this study is to describe, examine, and analyze the factors underlying Judges in implementing Judicial Activism practices in criminal cases in order to ensure the upholding of the Objectives of Law, namely Justice, Benefit and Certainty. Then what obstacles are faced, and parameters or benchmarks that can be done so that Judges can implement Judicial Activism in criminal cases. This study uses a sociological juridical approach method, with the research specification being descriptive analytical. The data used in this study are secondary data, obtained through literature studies which are then analyzed qualitatively using Progressive Legal Theory and the Theory of Judicial Freedom and Legal Discovery (Rechstvinding). The results of this study are: (1). Judges' decisions that apply Judicial Activism in criminal cases at least consider several factors, including legal developments that always follow a society that moves quickly, in addition, laws or other regulations are not always complete to solve a legal case concretely, and also several other factors. (2). Obstacles that arise in the practice of Judicial Activism in criminal cases are divided into two factors, namely internal factors that originate from the personality and emotionality of the judge himself, then external factors related to the legal system of a country. (3). The solution presented is to encourage judges to use their authority as guaranteed by the Law on Judicial institution to carry out rechtsvinding and not just apply the law (rechtoepassing) through the method of legal discovery, namely the interpretation method and the argumentation method.